Moderating effect of gender on self-esteem, work locus of control and job satisfaction of academicians in a public university in Yemen - Al Qubati, Ahlam Abdulbaqe Abdulmalik (2014)
Higher education system must aim at producing individuals who are well-educated, and equipped with the knowledge and skills to effectively participate in the development of the nation by meeting the human development demands rather than just provide mere education. Correspondingly the developing countries are facing great challenges in meeting the increasing demand for higher education, and to develop their institutions of higher education in order to keep pace with the developed nations of the contemporary world. Job satisfaction, which is a critical factor in the achievement of this objective, is too complex a phenomenon to be reduced to simple causal factor. A few studies of job satisfaction in higher education have been conducted and it was found that it is a very important criterion observed in enhancing the quality and logical organization of higher educational settings. Thus, to shed light on this essential point in the current study, the researcher focused on the impact of work locus of control and self-esteem of academic staff that was investigated with specific attention paid to how it affects several aspects of job satisfaction in universities of Yemen. This study was conducted to determine the level of job satisfaction among the academic staff. It investigates the relationship between self-esteem, work locus of control and job satisfaction as well as the role of gender as a moderation factor. The effects of facets of job satisfaction were observed and analyzed. The data were collected via self-report instruments. Data was collected from eight public Yemeni universities under the auspices of the Ministry of Higher Education (MOHE) located in all educational regions in Yemen. SPSS and Structural Equation Modeling (SEM) were used to analyze the data collected through questionnaires. Several important findings were achieved. The sample size was 573. The results indicated that the academic staff in the universities of Yemen have a high level of self-esteem, with a moderate level of job satisfaction and have external work locus of control. However, demographic factors such as gender, years of experience, academic rank were observed to have no influence on job satisfaction of academic staff in public universities in Yemen. In addition, further analyses on job satisfaction predictors such as self-esteem and work locus of control revealed that they were strong predictors of job satisfaction. There was a strong direct relationship between selfesteem, work locus of control and job satisfaction. The findings also indicated that gender has an impact in moderating the relationship between self-esteem and job satisfaction. The major contribution of this study is that it highlighted the role of selfesteem and work locus of control in job satisfaction and demonstrate the application of this effect on academics’ behavior. Universities must provide supportive human resource development practices and a conducive working environment that will nurture positive self-esteem and work locus of control among academics, which eventually will positively impact on their job satisfaction.